Variables associated to university instructors effectiveness based on the student's evaluations - Edna Luna Serrano; Vicente Arámburo Vizcarra (Arizona State University, 2013)
This project considers the relationship between the teaching effectiveness ratings and the variables associated to the (a) teacher and (b) group characteristics, such as: (a) education, work contract, external certification, years of teaching experience; and (b) academic field and group size. The sample was 4,482 courses, taught by 826 teachers that were evaluated by students 108,422 times, along six semesters at a public university in Mexico. The study was analyzed through descriptive and comparative statistic methods (Anova and post-hoc tests). The results show how the variables differ depending on the academic field, which reconfirms the teaching activity complexity and the difficulty to generate general policies that serve the particularities of every teacher's pedagogical context. This research presents empirical evidence that supports the discussion about teaching evaluation in Mexico and the assessment of the education policies that are targeted to the higher education teachers.